Os sentidos da escolha da profissão, por jovens de baixa renda: um estudo em psicologia sócio-histórica - Oliveira, Alessandra dos Santos (2009)
This study aimed to investigate the meanings that the young low-income have on the choice of profession. The results help to qualify the work of professional counselors who work with this social stratum. In this study, we used the theoretical framework of socio-historical psychology and we rely on authors who follow this theoretical perspective. We assume that all professional choice is multifactorial, and crossed by objective and subjective aspects. The question that arises is to identify, through analysis of their statements, the meanings they hold for career choice and all the factors that are related to this activity. To accomplish this work, we interviewed two people who had participated in a program of vocational guidance. A questionnaire prior to the interview and objective knowledge of the socioeconomic conditions of participants. For The interview technique was used Project Future , understanding it as an important resource for access to the senses of young people about the choice of profession. The results show that young people do not know the existence of factors that determine the choice of profession. However, their understanding of a dichotomy, therefore, tend to consider separately those aspects and the subjective process of choice